Policy Metrics for Coherent and Socially Inclusive Urban Transformation in Mobility and Energy (2022)
ABSTRACT: Chapter 8 considers the institutional and technological symbiotic interactions between energy and mobility within cities. The chapter proposes the combination of longitudinal analysis and ‘neighbouring’ analysis (identifying coupling between practises) using an analytical strategy to study these complex interactions.